Macroscopic Strain-Induced Transition from Quasi-infinite Gold Nanoparticle Chains to Defined Plasmonic Oligomers - Steiner, Anja Maria; Mayer, Martin; Seuss, Maximilian; Nikolov, Svetoslav; Harris, Kenneth D.; Alexeev, Alexander; Kuttner, Christian; Konig, Tobias A. F.; Fery, Andreas (ACS nano, 2017)
We investigate the formation of chains of few plasmonic nanoparticles - so-called plasmonic oligomers - by strain-induced fragmentation of linear particle assemblies. Detailed investigations of the fragmentation process are conducted by in situ atomic force microscopy and UV-vis-NIR spectroscopy. Based on these experimental results and mechanical simulations computed by the lattice spring model, we propose a formation mechanism that explains the observed decrease of chain polydispersity upon increasing strain and provides experimental guidelines for tailoring chain length distribution. By evaluation of the strain-dependent optical properties, we find a reversible, nonlinear shift of the dominant plasmonic resonance. We could quantitatively explain this feature based on simulations using generalized multiparticle Mie theory (GMMT). Both optical and morphological characterization show that the unstrained sample is dominated by chains with a length above the so-called infinite chain limit - above which optical properties show no dependency on chain length - while during deformation, the average chain length decrease below this limit and chain length distribution becomes more narrow. Since the formation mechanism results in a well-defined, parallel orientation of the oligomers on macroscopic areas, the effect of finite chain length can be studied even using conventional UV-vis-NIR spectroscopy. The scalable fabrication of oriented, linear plasmonic oligomers opens up additional opportunities for strain-dependent optical devices and mechanoplasmonic sensing.
CRIS-Team Scopus Importer:2022-04-14
Keywords: atomic force microscopy; generalized multiparticle Mie theory; plasmonic coupling; plasmonic nanoparticles; supra-colloidal assemblies; template-assisted colloidal self-assembly